Responsive building envelope concepts in zero emission neighborhoods and smart cities - A roadmap to implementation. (February 2019) - Taveres-Cachat, Ellika; Grynning, Steinar; Thomsen, Judith; Selkowitz, Stephen
Abstract: Designing a zero emission neighborhood (ZEN) from an energy point of view, has the benefit of distributing loads over time by creating a mosaic of buildings which individually may not have a zero emission balance, but reach it as an ensemble. Responsive building envelopes (RBEs) are expected to play an important role in the design of ZENs and future smart sustainable cities. RBEs are useful to optimize the balance between several energy flows at single- and multi building scale, as well as to actively manage both on-site renewable- and purchased energy in addition to improving user experience and indoor comfort by providing an interactive interface with the outdoors. This article provides a review of the potential and the requirements associated with using RBEs to manage complex interactions between buildings, clusters of buildings and utility grids. A six-step pathway for the implementation of RBEs in ZEN-like projects are proposed. The six steps are related to identifying; purpose of response, scale and interdependency, functionality, trigger and control, interactions and finally to identifying technical solutions. The proposed process emphasizes the importance of defining specific information such as the responsive goal hierarchies, the scale of the responses in relation to their purpose, and the importance of the aesthetic expression to foster positive user experience. Highlights: The possible benefits and challenges associated to applying responsive building design in zero emission neighborhoods are investigated. The existing frameworks for characterizing responsive building envelopes are reviewed and the knowledge gaps associated to neighborhood scale implementations are outlined. A roadmap building on previous knowledge and aimed at defining the necessary aspects which must be considered to successfully implement responsive building envelopes in a neighborhood context is proposed as a 6 step process. Future work and requirements for building performance analysis is discussed as the main challenge for planning responsive neighborhoods in the future.